The Influence Of Work Facilities, Competencies And Work Environment On The Performance Of Village Employees In Seluma District - Saputri, Andela; Anggriani, Ida; Wijaya, Ermy (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
competence and work environment on the performance of sub-district employees in Seluma District. The data collection method in this research used a questionnaire technique, with a sample of 70 respondents. The research results show that multiple linear regression Y = 2.812 + 0.372 X1 + 0.511 X2 + 0.186 X3 + 1.495. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between the variables work facilities (X1), competence (X2) and work environment (X3) on the performance of sub-district employees (Y) in Seluma District. The results show that the results of the work facilities test (XI) show tcount 2.704 > ttable 1.666 and significance 0.009 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning work facilities (XI) have a positive and significant effect on the performance of sub-district employees in the District Seluma. The results of the competency test (X2) show tcount 3.763 > ttable 1.666 and significance 0.000 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that competency (X2) has a positive and significant effect on the performance of sub-district employees in Seluma District. The results of the work environment test (X3) show tcount 3.113 > ttable 1.666 and significance 0.003 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning the work environment (X3) has a positive and significant effect on the performance of subdistrict employees in Seluma District and is based on comparing the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 39,588 > 2.50, so it is concluded that Accepting the Hypothesis, meaning that there is a simultaneous influence between work facilities (XI) competence (X2) and work environment (X3) on employee performance (Y) sub-district in Seluma District. This can be seen at the significance level of 0.000 <0.05